Effect of implementing decision support to activate a rapid response system by automated screening of verified vital sign data: A retrospective database study. (April 2022) - Jerng, Jih-Shuin; Chen, Li-Chin; Chen, Shey-Ying; Kuo, Lu-Cheng; Tsan, Chin-Yuan; Hsieh, Pei-Yin; Chen, Chien-Min; Chuang, Pao-Yu; Huang, Hsiao-Fang; Huang, Szu-Fen
Abstract: Aim: Activating a rapid response system (RRS) at general wards requires memorizing trigger criteria, identifying deterioration, and timely notification of abnormalities. We aimed to assess the effect of decision support (DS)-linked RRS activation on management and outcomes. Methods: We retrospectively analyzed general ward RRS activation cases from 2013 to 2017 and the incidence of cardiopulmonary resuscitations (CPR) from 2013 to 2020. A DS-alerting mechanism was added to the conventional RRS activation process in 2017, with an alert window appearing whenever the system automatically detected any verified abnormal vital sign entry, alerting the nurse to take further action. Logistic and linear regression analyses were used to compare outcomes. Results: We analyzed 27, 747 activations and 64, 592 DS alerts. RRS activations increased from 3.5 to 30.3 per 1, 000 patient-days ( P  < 0.001) after DS implementation. The first DS activations occurred earlier than conventional ones (−2.9 days, 95% confidence interval = −3.6 to −2.1 days). After adjustment with inverse probability of treatment weighting, main (conventional vs DS-linked activations after implementation) and sensitivity analyses showed that DS activation cases had a lower risk of CPR and in-hospital mortality. Cases with more DS alerts before RRS activation had a higher risk of CPR ( P trend = 0.017) and in-hospital mortality ( P trend < 0.001). The incidence of CPR at the general ward decreased. Conclusion: Implementing a DS mechanism with an automated screening of verified abnormal vital signs linked to RRS activations at general wards was associated with improved practice and timeliness of hospital-wide RRS activations and reduced in-hospital resuscitations and mortality.